MECHANICAL ANALYSIS ON TEST SAMPLES MADE IN CONCRETE REINFORCED WITH STEEL FIBERS - Chaves Pabón, Saieth Baudilio; Ospina García, Miguel Angel; Bonet León, Miguel Ángel (Journal of Applied Engineering Science, 2024)
Steel fibers have been used for improving the behavior of structural concrete elements for a long time ago. This paper shows the main results from the flexural test of steel fiber reinforced concrete beams, that is to say, flexural strength and toughness. The results were compared with those from the flexural test of reinforced concrete beams with steel bars and plain concrete beams. Steel fiber did not increase the flexural strength and toughness of beams when compare with reinforced beams with steel bars but it does improve the behavior of steel fiber reinforced concrete beams for failure control and gradual mechanics which allows caution about upcoming collapse.
Keywords: flexural strength, toughness, steel fiber, steel bar